Willingness to pay in main cities of Zheijiang provice (China) for quality and safety in food market. (February 2020) - Riccioli, F.; Moruzzo, R.; Zhang, Z.; Zhao, J.; Tang, Y.; Tinacci, L.; Boncinelli, F.; De Martino, D.; Guidi, A.
Abstract: Food safety related incidents have increased consumers' concern about food safety and quality and led to a distrust in the Chinese food market. This paper investigates how sociodemographic variables affect willingness to pay (WTP) both for safer and higher quality food by identify a specific user profile. Data were collected through a consumer survey conducted in Hangzhou, Zhejiang Province, administrating 1000 questionnaires, 757 of which resulted valid. Data showed that level of education, income, being married and the place of purchase significantly influences the WTP while the ages does not affect it. WTP is elicited by using a payment card method, and its estimation is performed with interval data regression model. Results also indicates that "food quality" and "food safety" have the same impact level on the WTP, indicating certain confusion about their significance. Other study results and implication on informative and educative policies are discussed. Highlights: Paper analyse the perception that a sample of people has of food safety and quality. Over 700 questionnaires distributed in China (Hangzhou, Zhejiang Province). We asked WTPs more than standard price for safer and higher quality rice. In order to test how variables explored affect WTPs, interval data regression was performed.